1993
DOI: 10.1152/jappl.1993.74.1.297
|View full text |Cite
|
Sign up to set email alerts
|

Atypical beta-adrenoceptor- (beta 3-adrenoceptor) mediated relaxation of canine isolated bronchial smooth muscle

Abstract: To determine whether atypical beta-adrenoceptors (beta 3-adrenoceptors) exist in the airway smooth muscle, we studied isolated bronchial segments from dogs under isometric conditions in vitro. Addition of beta-adrenoceptor agonists produced a concentration-dependent relaxation of tissues precontracted with 10(-5) M acetylcholine, rank-order potency being isoproterenol (1) > or = salbutamol (0.95) > or = BRL 37344, a beta 3-selective adrenoceptor agonist (0.83) > norepinephrine (0.10). Under the condition that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
2
16
1
Order By: Relevance
“…Our results have clearly shown that in the three species studied, and under the experimental conditions selected, an intense relaxation of the bronchial smooth muscle can be obtained with salbutamol and isoprenaline, and that this effect is principally β 2 -adrenergic, since the relaxations induced by these substances are abolished by ICI 118,551 10 -6 M, a concentration at which this substance can be considered a specific antagonist of β 2 -adrenoceptors [10]. However, we observed that on sheep bronchi salbutamol has a partial agonistic effect that is weaker than in human and guinea pig bronchi, as testified by a lower Emax.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Our results have clearly shown that in the three species studied, and under the experimental conditions selected, an intense relaxation of the bronchial smooth muscle can be obtained with salbutamol and isoprenaline, and that this effect is principally β 2 -adrenergic, since the relaxations induced by these substances are abolished by ICI 118,551 10 -6 M, a concentration at which this substance can be considered a specific antagonist of β 2 -adrenoceptors [10]. However, we observed that on sheep bronchi salbutamol has a partial agonistic effect that is weaker than in human and guinea pig bronchi, as testified by a lower Emax.…”
Section: Discussionmentioning
confidence: 55%
“…A recent paper by TAMAOKI et al [10] reported that β 3 -adrenoceptor stimulation mediated relaxation of isolated canine bronchial smooth muscle. The aim of the present study was to extend this observation to other species.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown in dose in Finnish subjects showed that the mutation frequency was similar in non-diabetic subjects (12%) and subjects response studies with BRL 37344 in canine bronchial smooth muscle that b 3 -AR mediate bronchorelaxant with NIDDM (11%), although the mean age for onset of diabetes was lower in those with the mutation [ 42]. effects [30 ], whilst other data have suggested a role of b 3 -AR in mediation of prejunction inhibition of nonIn the non-diabetic subjects, those with the mutation exhibited a greater degree of obesity and impaired adrenergic non-cholinergic contraction in guinea-pig bronchus [ 31]. However, Martin et al have subinsulin sensitivity.…”
Section: Molecular Pharmacological Studiesmentioning
confidence: 95%